Pelatihan Penulisan Esai Berbasis Budaya Lokal Pada Siswa SMA/SMK Di Kabupaten Minahasa Selatan - Pandean, Mariam; Palit, Anatje Tinike; Karouw, Stella (Servitium Smart Journal, 2025)
Writing is a skill to express ideas or thoughts in written form. Essay writing is relatively short because it only contains certain topics or reviews in the form of criticism/suggestions or opinions that are delivered coherently and have coherence so that they can be easily understood. Essay topics about culture are intended to foster a sense of love and pride in the local culture of each region. The purpose of this training activity is to train high school/vocational school students to write essays on the theme of local culture. This activity was carried out on August 6, 2024 at SMK Negeri I Tareran Minahasa Selatan. The method used was in the form of training and mentoring in writing essays. The results obtained by all participants or students totaling 75 students have been able to write essays with various local cultural themes. This result is very visible in the increase in competency that students initially did not have, after this training activity, a significant increase was obtained from participants regarding their ability to write essays and produced 75 essays on the theme of culture.  Keywords— Language, Writing, Author, Essay Writing, Local Culture.